The code breaker : Jennifer Doudna, gene editing, and the future of the human race - Isaacson, Walter (Simon & Schuster, 2021)
In 2012, Nobel Prize winning scientist Jennifer Doudna hit upon an invention that will transform the future of the human race: an easy-to-use tool that can edit DNA. Known as CRISPR, it opened a brave new world of medical miracles and moral questions. It has already been deployed to cure deadly diseases, fight the coronavirus pandemic of 2020, and make inheritable changes in the genes of babies. But what does that mean for humanity?